Peran Komite Sekolah Dalam Implementasi Manajemen Berbasis Sekolah di SDN 1 Kanoman - Yulinda Anggun Prasasti; Sofwan Adi Putra; Arman Arman; Juhri Abdul Mu’in (Journal of Innovative and Creativity, 2026)
This study aims to analyze the role of the School Committee in the implementation of School-Based Management at SDN 1 Kanoman. School-Based Management emphasizes greater autonomy for schools as well as the principles of participation, transparency, and accountability in educational management. This research employed a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, observation, and documentation studies involving the principal, teachers, and school committee members as the main sources of information. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results indicate that the School Committee has carried out its roles as an advisory body, supporting body, controlling body, and mediator. However, the implementation has not been fully optimal, as the committee’s role is still mainly focused on administrative matters and financial support. This study concludes that strengthening understanding and continuous capacity building are necessary to enhance the effectiveness of the School Committee’s role in School-Based Management.